Odpowiedzi

Najlepsza Odpowiedź!
2009-11-17T14:27:43+01:00
4y+2+2(2y²-3y-1-y²-8)=4y+2+4y²-6y-2-2y²-16=2y²-2y-16
w tym przykładzie jest błąd powinno być
4y+2+2(2y²-3y-1-y²-8)=4y+2+4y²-6y-2-2y²+16=2y²-2y+16

2(2y²-3y-1)-(4y+2)+y²+8=4y²-6y-2-4y-2+y²+8=5y²-10y+4

3(4y+2)-2(2y²-3y-1)-(y²+8)=12y+6-4y²+6y+2-y²-8=-5y²+18y
2009-11-17T14:29:03+01:00
A)
4y+2+2(2y (kwadrat)-3y-1-y(kwadrat)+8
4y+2+4y(kwadrat)-6y-2-2y(kwadrat)+16
2y(kwadrat)-2y+16
2009-11-17T14:33:18+01:00
A+2(B-C)=
4y+2+2(2y^-3y-1-y^+8)=4y+2+2(4y^-3y-1-y^+8)=4y+2+8y^-6y-2-2y^+16=-2y+6y^+16

2B-A+C=
2(2y^-3y-1)-4y+2+y^+8=2y^-6y-2-4y+2+y^+8=3y^-10y+12

3A-2B-C=
3(4y+2)-2(2y^- 3y-1)-y^+8=12y+6-4y^+6y+2-y^+8=18y-5y^+16


^-To jest do kwadratu
1 5 1